Evaluation of the effectiveness of marketing innovations - Tkachova, N. P.; Pererva, P. G. (My University, 2023)
The versatility and variability of various methodological approaches to the assessment of the marketing innovation activity of enterprises necessitates a comprehensive approach to determining the dynamics of innovation processes based on one of the integral criteria, which can be an indicator of the innovative activity of marketing. enterprise activity. Therefore, the development of methodical approaches to the evaluation of the economic efficiency of marketing innovations and the justification of the choice of the strategy of innovative development of the enterprise is relevant.
Оцінка ефективності маркетингових інновацій
Keywords: innovative activity; marketing; demand formation; sales promotion; performance evaluation